The Effect of the Degree of Anxiety of Learners during the Use of VR on the Flow and Learning Effect - Chongsan Kwon (Applied Sciences, 2020)
Virtual reality (VR) learning content that provides negative experiences makes learners anxious. Thus, experimental research was conducted to determine how anxiety felt by learners using VR impacts learning. To measure the learning effects, flow, a leading element of learning effects, was measured. Flow has a positive effect on learning as a scale of how immersed an individual is in the work he or she is currently performing. The evaluation method used the empirical recognition scale by Kwon (2020) and the six-item short-form State-Trait Anxiety Inventory (STAI) from Marteau and Becker (1992), which were used in the preceding study. The difference in flow between high- and low-anxiety groups was explored by measuring the degree the study participants felt using an Fire Safety Education Game based on VR that allows learners to feel the heat and wind of the fire site with their skin. As a result of the experiment, no difference in flow was found between the high- and low-anxiety groups that played the same VR game with cutaneous sensation. However, the high-anxiety group who played the VR game with cutaneous sensation showed a higher flow than the group that played the basic fire safety education VR game. Based on these results, the following conclusions were drawn: the closer to reality the VR learning and training system for negative situations is reproduced, the more realistically the learner feels the anxiety. In other words, the closer to reality the virtual environment is reproduced, the more realistically the learner feels the feelings in the virtual space. In turn, through this realistic experience, the learner becomes immersed in the flow more deeply. In addition, considering that flow is a prerequisite for the learning effect, the anxiety that learners feel in the virtual environment will also have a positive effect on the learning effect. As a result, it can be assumed that the more realistically VR is reproduced, the more effective experiential learning using VR can be.